2021
DOI: 10.3390/membranes11080570
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Identification of Cholesterol Binding Motifs in the Chemokine Receptor CCR3

Abstract: CC motif chemokine receptor 3 (CCR3) is a Class A G protein-coupled receptor (GPCR) mainly responsible for the cellular trafficking of eosinophils. As such, it plays key roles in inflammatory conditions, such as asthma and arthritis, and the metastasis of many deadly forms of cancer. However, little is known about how CCR3 functionally interacts with its bilayer environment. Here, we investigate cholesterol binding sites in silico through Coarse-Grained Molecular Dynamics (MD) and Pylipid analysis using an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 108 publications
2
22
0
Order By: Relevance
“…Among lipids, cholesterol is the most important allosteric regulator of GPCRs, and its effects on receptor activity are highly dependent on the content of cholesterol in the membrane, the type of receptor, and the nature of the orthosteric ligand [91,132,133]. A significant number of GPCRs contain consensus motifs for cholesterol binding (Cholesterol Recognition/Interaction Amino Acid Consensus motif, CRAC), which were first identified in β2-AR [134] and then found in other GPCRs, although often in modified form [91,135,136]. Along with cholesterol, other lipids are involved in the allosteric regulation of GPCRs, including phosphatidylinositol-4,5-bisphosphate, phosphoinositols [90] and phosphoserines [89].…”
Section: Diversity Of Endogenous Allosteric Regulators Of Gpcrsmentioning
confidence: 99%
“…Among lipids, cholesterol is the most important allosteric regulator of GPCRs, and its effects on receptor activity are highly dependent on the content of cholesterol in the membrane, the type of receptor, and the nature of the orthosteric ligand [91,132,133]. A significant number of GPCRs contain consensus motifs for cholesterol binding (Cholesterol Recognition/Interaction Amino Acid Consensus motif, CRAC), which were first identified in β2-AR [134] and then found in other GPCRs, although often in modified form [91,135,136]. Along with cholesterol, other lipids are involved in the allosteric regulation of GPCRs, including phosphatidylinositol-4,5-bisphosphate, phosphoinositols [90] and phosphoserines [89].…”
Section: Diversity Of Endogenous Allosteric Regulators Of Gpcrsmentioning
confidence: 99%
“…2e). The methodological underpinnings of PyLipID are described extensively elsewhere 24 and have been applied to a number of recent examples [31][32][33] .…”
Section: Pipeline Implementationmentioning
confidence: 99%
“…We investigate mutants of G137, L140, and F149 in TM2 that are involved in the main channel activation allosteric network. These functional data are paired with coarse grain molecular dynamics (CGMD) simulations in an activating, PG-rich environment using the Martini Forcefield. , MD experiments have been used to good effect to characterize large macromolecular complexes such as protein–protein interactions, protein–lipid interactions, ,, and conformational dynamics of biomolecules. These in silico experiments contextualize the effect of mutation on how PG interacts with KirBac1.1 via PyLipID analysis . It was found that loss of PG residency time on gating arginine residues as a function of mutation in silico was correlated with flux in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…These functional data are paired with coarse grain molecular dynamics (CGMD) simulations in an activating, PG-rich environment using the Martini Forcefield. 33 , 34 MD experiments have been used to good effect to characterize large macromolecular complexes such as protein–protein interactions, 35 40 protein–lipid interactions, 19 , 20 , 41 and conformational dynamics of biomolecules. 42 46 These in silico experiments contextualize the effect of mutation on how PG interacts with KirBac1.1 via PyLipID analysis.…”
Section: Introductionmentioning
confidence: 99%